Para além do muro de Berlim: as relações Brasil/Alemanha Oriental - Blumenhagen Junior, Frederico Antonio Ridder de [UNIFESP] (2016)
In 1973 Brazil officially recognized the German Democratic Republic (GDR) and a number of deals, treaties and protocols were signed between the two states. Despite the exchange of embassies only happening in the early 1970?s, commercial relations between the two countries had been increasing since the end of the 1950?s, with a leap in the 1960?s, when Brazil?s foreign policies increasingly became more autonomist and universalist. Given this, we propose a study of the history and the content of the Brazilian/GDR relations from this new diplomatic concept, which in the 1960?s and 1970?s, cosubstantiated a new paradigm of international insertion: the paradigm of autonomy. With this study we intend to enlighten a theme still understudied in the history of Brazilian Foreign Policy, the relations between Brazil and a country located in the zone of Soviet influence in a context marked by the Cold War. We also discuss how the paradigm shift of the Brazilian Diplomacy, as well as the concepts and conceptions forged by it, can be used as theoretical basis for the study of Brazilian international relations.